Penilaian Kinerja Pengelolaan Sampah Daerah Kabupaten Bolaang Mongondow Timur, Sulawesi Utara - Muh. Nuruzzaman Hattam; Bieby Voijant Tangahu (Jurnal Serambi Engineering, 2024)
Environmental management plays an important role in regional development by supporting sustainable development. One of the challenges in East Bolaang Mongondow Regency is the problem of waste management in the form of limited waste management facilities and infrastructure, especially the availability of landfills. Based on these conditions, in order to determine the effectiveness of waste management, it is necessary to conduct research on waste management performance in the Regency. Boltim. Efforts to assess waste management performance in Kab. Boltim include: first, analysing service aspects based on normative standards by comparing data on the amount of waste transported, the population served and the area served; and based on the concept of environmental sustainability, a quantitative descriptive analysis of the community's views on various aspects that influence waste management. Based on normative standards, the waste management performance in Kab. Boltim was 10.23% of the wast e transported, covering an area of 21.64%. Waste management in the district. Boltim does not support the application of the concept of environmental sustainability in all aspects of waste management.